2023
DOI: 10.1021/acs.inorgchem.3c00438
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Intercalated Zirconium Phosphate by Granulation: A Strategy for Enhancing Adsorption Selectivity of Strontium and Cesium from Liquid Radioactive Waste

Abstract: The capture of the radionuclides strontium and cesium is of great importance to the environment, human health, and the sustainable development of nuclear energy, and zirconium phosphate with excellent ion exchange capacity has potential application in this field. In this work, we organically granulated zirconium phosphate to induce the formation of composite bead materials (CA@ZrP) with a calcium-containing phase with selectivity for Sr 2+ and Cs + higher than that of pure ZrP in low-pH environments and compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Moreover, since the powder properties of Ag@PPy would limit further large-scale column test, we propose several strategies to prepare micron-scale bead-like composites appropriate to actual field situations. Polyethersulfone, polyacrylonitrile and sodium alginate have been chosen as support hosts for composite granulation, 15,68 and cross-scale macro-assembled composites are expected to be applied to iodine removal in actual liquid waste systems. These future challenges also provide us a new opportunity to fully explore the benefits of silver-based polymers in the remediation of iodine-contaminated water.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, since the powder properties of Ag@PPy would limit further large-scale column test, we propose several strategies to prepare micron-scale bead-like composites appropriate to actual field situations. Polyethersulfone, polyacrylonitrile and sodium alginate have been chosen as support hosts for composite granulation, 15,68 and cross-scale macro-assembled composites are expected to be applied to iodine removal in actual liquid waste systems. These future challenges also provide us a new opportunity to fully explore the benefits of silver-based polymers in the remediation of iodine-contaminated water.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the presence of calcium-containing phases can achieve this effect. 41 Although the corresponding calcium intercalated zirconium phosphates have been reported, their crystalline phase structure and their application in adsorption have not been precisely investigated. 42–44 The reported preparation of pure CaZr(PO 4 ) 2 was synthesized at high temperatures, removing the interlayer water and making the interlayer spacing compressed unfavorable for ion exchange.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing demand of carbon-neutral and low-cost energy has caused nuclear energy to become an essential element in the overall composition of the current global power supply. Accompanied by the high-speed development of nuclear energy, the environmental problems associated with used nuclear fuel have aroused great attention. Of the spent fuel produced by modern light water reactors, over 98.5% of the components are mainly composed of U, Pu, and lanthanides (Ln) . However, it still contains less than 1 wt % of minor actinides (MA) including Am, Np, and Cm, which are responsible for long-standing radiotoxicity. In order to improve the long-term management safety of nuclear waste, the partitioning-transmutation strategy (P&T) was emerged and recognized as a viable global option. , The proposed P&T initially partitioned the transuranic elements and long-lived fission products by the PUREX process using solvent extraction, , and they were subsequently subjected to neutron bombardment for transmutation into short-lived nuclides .…”
Section: Introductionmentioning
confidence: 99%